Quo Vadis: A Narrative of the Time of Nero - Sienkiewicz, Henryk, 1846-1916; Curtin, Jeremiah, 1835-1906 (Salt Lake City, UT : Project Gutenberg, 2001)
"Quo Vadis: A Narrative of the Time of Nero" by Henryk Sienkiewicz is a historical novel written in 1895-1896. Set in ancient Rome during Nero's reign, it follows the forbidden romance between Marcus Vinicius, a Roman patrician, and Lygia, a Christian woman and hostage. As their love develops against the backdrop of imperial decadence, the Great Fire of Rome ignites, leading Nero to brutally persecute Christians as scapegoats. The novel weaves together personal passion, religious faith, and historical events in a gripping tale of survival. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Quo_Vadis_(novel)
Release date is 2001-10-01
Produced by David Reed, and David Widger
Keywords: Historical fiction; Church history -- Primitive and early church, ca. 30-600 -- Fiction; Rome -- History -- Nero, 54-68 -- Fiction; Christian fiction